Profiling online gamers and probing their preferences and motivations: An empirical study of an online role-playing game. Issue 3 (1st October 2021) - Chu, Chau; Halme, Merja; Merikivi, Jani; Penttinen, Esko
Greater understanding of gamers' preferences (what it is in the game that they value) and motivations (why they play the game) provides cues for game developers' better response to consumer desires and drives. Complementing insights from literature that identifies a wide variety of antecedents to both preferences and motivations, the article addresses the relationship between the two by reporting on an empirical study in the context of online role-playing. In the study, analysis of gamer preferences revealed five gamer clusters (storyline-lovers, aesthetics-lovers, socializers, achievers and local-story-lovers), which together reflect three key gamer motivations (achievement related, social and immersion based). In a key finding, immersion emerged as an overarching motivator, spanning all the clusters and different in nature from the other two motivating factors. Also, distinguishing between local- and global-storyline-lovers may have important implications. Thirdly, the authors make a methodological contribution connected with the design of best‐worst scaling, thereby informing managerial insights and providing avenues for further research.